Fabrication of durable and flexible single-walled carbon nanotube transparent conductive films. Issue 31 (31st March 2017) - Devaraju, Subramani; Lee, Taeheon; Mohanty, Aruna Kumar; Hong, Young Kun; Yoon, Kwan Han; Lee, Young Sil; Han, Jong Hun; Paik, Hyun-jong
Abstract : Highly flexible, durable, and transparent conducting films are fabricated from the de-bundled SWCNTs in aqueous solutions of SPES with high conductivity (125 Ω sq −1 ) and good transmittance (87%) without adopting any binder or post treatment techniques. Abstract : In the present work, flexible, durable, transparent, conductive films (TCFs) were fabricated with the use of aqueous dispersed single-walled carbon nanotubes (SWCNTs). A small amount of the synthesized sulfonated poly(ether sulfone) (SPES) was used to effectively disperse SWCNTs with high aspect ratios. The lengths and heights of the dispersed SWCNTs were 2.5 ± 1.0 μm and 2 ± 1 nm, as determined by TEM and AFM, respectively. TCFs were fabricated using spray coating on a PET substrate; the best performance among the TCFs was achieved with a sheet resistance ( R s ) of 125 Ω sq −1 and optical transmittance of 87.1%. Moreover, no appreciable change in the R s was observed after repeated bending cycles and adhesive peel-off tests, which indicate that SPES acts as a good dispersant and effective binder for the improvement in durability and adhesion behavior of the resulting TCFs in the absence of additional binders. Therefore, this material holds great potential for scalable and facile production of flexible SWCNT-TCFs for various electronic applications.